Clusters of strength: a case study of the educational resilience of a post-institutionalized adopted child from Eastern Europe - Flagler, Marita Nika, author; Banning, James H., advisor; Granger, Ben P., committee member; Schell-Frank, Deborah, committee member; Lehmann, Jean, committee member (Colorado State University. Libraries, 2004)
Resilience is the human capacity to face, overcome and even be strengthened by experiences of adversity. Educational resilience is manifested through the school success of at-risk students. The interest in educational resilience is rooted in the huge impact that academic success or failure has on adult life outcomes. This study was designed to advance the understanding of resilience in general and educational resilience in particular. Post-institutionalized adoptees from Eastern Europe were selected as the target population of the study. There is a general consensus among professionals working with adopted post-institutionalized children from Eastern Europe that this is a high-risk group due to a combination of personal and environmental risk factors. Of these factors, the physical, social and psychological impact of life in an institution seems to be the most significant. Nevertheless, many of the about fifty thousand children, adopted from Eastern European orphanages since 1989, have shown remarkable resilience. A case study design was selected for the research as the methodology that permitted the use of an ecological-transactional-developmental approach, which a thorough literature review determined to be appropriate in understanding the mechanism of resilience. A 12-year-old post-institutionalized international female adoptee from Russia, who was taking regular education classes and had a cumulative GPA of 2.96 was selected to be subject of the case study. The data were gathered through taped interviews, questionnaires, observations, documents, relevant publications in the local press and student's self-expression. The work of risk and protection factors that shaped the student's development and had an impact on her educational outcomes is analyzed thoroughly and then presented graphically through the model of the resultant vector. Among theoretical implications, the most important posits that the mere existence of assets, resources and other personal and social capital per se may not guarantee their activation as protective factors. They seem to be triggered and mediated via mindfulness. Practical implications focus on the need for post-adoption services to include a school advocate. At the end, directions for future research comprise a proposal to introduce the theory of mindfulness and the constructs of mindfulness and mindlessness to the resilience discourse.
Keywords: social work